ANALISIS EFEKTIVITAS, EFISIENSI PAJAK DAERAH DAN RETRIBUSI DAERAH SERTA KONTRIBUSI TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN BANTUL TAHUN 2009-2014 - Ryfal Yoduke; Sri Ayem (Jurnal Akuntansi, 2015)
The study was conducted in Bantul, for research purposesprovides an overview of (1) the effectiveness of the tax year dearah to PAD2009-2014; (2) efficiency at local levies to PAD 2009-2014; (3)Local Tax contribution to PAD for 2009-2014;(4) contribution levies Area to PAD 2009-2014.The nature of the research include descriptive, population is the report Bantul year's actual revenue and budget realization report service producer Retribution 2009-2014, also at the same till. Method Data collection is a method of secondary data, as well as techniques to analyze the data using the ratio of effectiveness, efficiency ratio, and the ratio of contribution. The study found that the level of effectiveness of the Local Tax 2009, 2011, 2012, 2013, 2014, very effective, and in 2010 effective. Level Retribution efficiency 2009-2014, entirely exceeded 100% andotherwise very ineffective. Local Tax contribution in 2009 at the level ofless; In 2010, 2011, 2014 moderate; 2012 and 2013 is quite good. Contributions Retribution 2009 at a very good level, 2010-2013 criteria is less,2014 is very less. Keywords: Effectiveness and Efficiency, Contributions, Local Taxes and Levies, PAD